2023
DOI: 10.3390/economies11040111
|View full text |Cite
|
Sign up to set email alerts
|

Sharia Economy, Islamic Financial Performance and Factors That Influence It—Evidence from Indonesia

Abstract: The contribution of SMEs to economic growth is supported by the development of the sharia economy by the government, making SMEs one of the main pillars in Indonesia’s economic development. This study aimed to analyze the influence of the digital economy, financial literacy, human capital, the role of Islamic financial institutions, government support for strengthening the Islamic economy and the Islamic financial performance of SMEs in Makassar City, Indonesia. This study used a quantitative method with a sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 90 publications
0
2
0
1
Order By: Relevance
“…Integrasi yang kuat antara aspek keuangan, manajerial, strategis, dan nilai-nilai agama dapat membantu meningkatkan kualitas perencanaan anggaran di institusi tersebut. Pengaruh konteks eksternal, termasuk regulasi pemerintah dan kondisi ekonomi, juga memainkan peran penting dalam proses perencanaan anggaran di perguruan tinggi agama Islam, seperti yang disoroti dalam penelitian literatur oleh Menne et al, (2023). Regulasi pemerintah yang berkaitan dengan pendanaan dan kebijakan pendidikan dapat mempengaruhi cara institusi merencanakan, mengalokasikan, dan menggunakan anggaran mereka.…”
Section: Pembahasanunclassified
“…Integrasi yang kuat antara aspek keuangan, manajerial, strategis, dan nilai-nilai agama dapat membantu meningkatkan kualitas perencanaan anggaran di institusi tersebut. Pengaruh konteks eksternal, termasuk regulasi pemerintah dan kondisi ekonomi, juga memainkan peran penting dalam proses perencanaan anggaran di perguruan tinggi agama Islam, seperti yang disoroti dalam penelitian literatur oleh Menne et al, (2023). Regulasi pemerintah yang berkaitan dengan pendanaan dan kebijakan pendidikan dapat mempengaruhi cara institusi merencanakan, mengalokasikan, dan menggunakan anggaran mereka.…”
Section: Pembahasanunclassified
“…In this context, Muslims must attain Islamic financial literacy (IFL), which entails the level of financial understanding necessary to adopt the best practices for serving humanity (Dinc et al, 2021). According to various research-based metrics for measuring financial literacy, Menne et al (2023) identified several indicators: knowledge of Islamic financial products, the ability to use financial products, the capability to prepare financial reports, and the ability to read financial reports. et al (2018) define "fintech" as the use of technology to enhance the efficiency of the financial system and the provision of financial services.…”
Section: Islamic Financial Literacymentioning
confidence: 99%
“…Consequently, it is essential for Muslims to possess Islamic financial literacy (IFL); they must have sufficient financial knowledge within an Islamic framework to behave ethically and idealistically for the benefit of humanity (Dinc et al, 2021). However, the low level of relevance indicates that MSMEs have not fully comprehended or leveraged Islamic financial literacy (Menne et al, 2023). Alharbi et al (2022) noted that due to the Islamic environment and business location, MSME managers only need a basic understanding of finance to develop their businesses effectively.…”
Section: Introductionmentioning
confidence: 99%